KEEFEKTIFAN MEDIA FLORABOX DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV SD - Laura Amalia; Asmaul Lutfauziah; Muslimin Ibrahim; Muhammad Thamrin Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low science learning motivation of elementary school students because learning media had not been used effectively. The purpose of this study was to determine the effectiveness of the Florabox media in improving students’ learning motivation. This study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design involving 34 fourth-grade elementary school students. The instrument used was an ARCS learning motivation questionnaire. The data were analyzed using the N-gain test. The results showed that the Florabox media was potentially effective in improving students' learning motivation, as indicated by an average N-gain score of 0.826, which was classified as high.